Graphene-coated molybdenum dioxide nanorod composite material as well as preparation method and application thereof
By using a core-shell structure to encapsulate molybdenum dioxide nanorods in graphene, the adsorption selectivity and conductivity issues of existing electrode materials are solved, achieving efficient and stable lead ion removal, which is suitable for capacitive deionization technology.
Patent Information
- Application Number
- CN202511381026.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-25
- Publication Date
- 2026-01-23
AI Technical Summary
Existing electrode materials exhibit low selectivity for lead ion adsorption in capacitive deionization technology, poor conductivity, and difficulty in precisely controlling coating thickness, which affects removal efficiency and stability.
A graphene-encapsulated molybdenum dioxide nanorod composite material was developed by in-situ polymerization and high-temperature calcination to form a core-shell structure. The graphene layer, with a thickness of 10-80 nm, provides high conductivity and protection, while the molybdenum dioxide core provides adsorption sites, thus optimizing the material's conductivity and adsorption performance.
It significantly improves the adsorption capacity and removal efficiency of lead ions, as well as the material stability and cycle life. The removal rate can reach 100% within 40 minutes and remains above 90% after 10 cycles, achieving efficient and economical lead ion removal.
Smart Images

Figure CN121372322A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of water treatment, and particularly relates to a graphene-wrapped molybdenum dioxide nanorod composite material and a preparation method and application thereof. BACKGROUND
[0002] With the rapid development of industry, the discharge of lead-containing wastewater has caused serious threats to the environment and human health. Lead is a heavy metal with biological accumulation, which can cause irreversible damage to the nervous system, blood system and kidney of the human body even at low concentrations. Therefore, it is of great environmental and social significance to efficiently remove lead ions in wastewater.
[0003] Capacitive deionization technology (CDI) as a new water treatment technology has shown broad application prospects in the field of heavy metal ion removal due to its low energy consumption, no secondary pollution and recyclability. The core of capacitive deionization technology is electrode material, and its performance directly determines the removal efficiency and cycle stability. At present, commonly used electrode materials include carbon-based materials (such as activated carbon, carbon nanotubes, graphene, etc.) and metal oxide materials (such as manganese dioxide, titanium dioxide, etc.). However, carbon-based materials have low adsorption selectivity for lead ions, which makes it difficult to efficiently remove lead ions in complex wastewater systems; although metal oxide materials have certain adsorption performance, their poor electrical conductivity limits the electron transport efficiency in the capacitive deionization process, which further affects the removal effect.
[0004] CN116803909A discloses a composite material, an electrode loaded with the composite material and a preparation method. The composite material is a composite of cerium oxide and carbon nanotubes, which forms a tight coating structure through annealing reaction, and is used as a selective electrode in capacitive deionization technology to achieve efficient removal of fluoride ions in groundwater. However, in the preparation process of the above-mentioned composite electrode material, the thickness of the carbon layer is often difficult to accurately control. If the carbon layer is too thin, the core material cannot be effectively protected, which leads to the dissolution or agglomeration of the core material under the influence of the external environment; if the carbon layer is too thick, it will shield the active sites of the core material, reducing the adsorption performance of the material.
[0005] Therefore, it is urgent to develop a new type of electrode material with high electrical conductivity, high adsorption selectivity and controllable wrapping thickness to improve the removal efficiency of lead ions by capacitive deionization technology. SUMMARY
[0006] The purpose of the present application is to overcome the defects of the prior art and provide a graphene-wrapped molybdenum dioxide nanorod composite material and a preparation method and application thereof.
[0007] The purpose of the present application can be achieved by the following technical solutions:
[0008] The application provides a graphene-wrapped molybdenum dioxide nanorod composite material, which is a core-shell structure with a molybdenum dioxide nanorod as the core and a graphene layer as the shell.
[0009] The graphene layer is formed by high-temperature carbonization of polyaniline, and the thickness of the graphene layer is 10-80 nm.
[0010] Further, the diameter of the molybdenum dioxide nanorod is 100-400 nm.
[0011] Further, the length of the molybdenum dioxide nanorod is 6-10 μm.
[0012] Further, the thickness of the graphene layer is preferably 20-70 nm, and further preferably 50-60 nm.
[0013] The application also provides a preparation method of the graphene-wrapped molybdenum dioxide nanorod composite material, which comprises the following steps:
[0014] S1: dissolving a molybdenum source in an aqueous nitric acid solution to perform a hydrothermal reaction, and preparing a molybdenum trioxide nanorod precursor;
[0015] S2: dispersing the molybdenum trioxide nanorod precursor prepared in S1 in an acidic solution, and adding aniline and ammonium persulfate in sequence under stirring to obtain a polyaniline / molybdenum trioxide composite precursor;
[0016] S3: drying the polyaniline / molybdenum trioxide composite precursor obtained in S2 and performing high-temperature calcination to obtain the graphene-wrapped molybdenum dioxide nanorod composite material.
[0017] Further, in step S1, the molybdenum source comprises any one or more of ammonium heptamolybdate tetrahydrate, ammonium thiomolybdate, sodium molybdate and calcium molybdate, and is preferably ammonium heptamolybdate tetrahydrate.
[0018] Further, in step S1, the concentration of the molybdenum source in the aqueous nitric acid solution is 0.02-0.35 mol / L.
[0019] Further, in step S1, the concentration of nitric acid in the aqueous nitric acid solution is 1.44-3.95 mol / L.
[0020] Further, in step S1, the temperature of the hydrothermal reaction is 180-220 ℃, and is preferably 200 ℃.
[0021] Further, in step S1, the time of the hydrothermal reaction is 2-10 h, and is preferably 6 h.
[0022] Further, in step S2, the mass ratio of the molybdenum trioxide nanorod precursor, aniline and ammonium persulfate is (8-10):(3-11):(20-24).
[0023] Further, in step S2, the mass concentration of the molybdenum trioxide nanorod precursor in the acid solution is 8-12.5 mg / mL.
[0024] Further, in step S2, the acid solution is a hydrochloric acid solution with a concentration of 1.9-2.1 mol / L.
[0025] Further, in step S2, the molybdenum trioxide nanorod precursor is dispersed in the acid solution by ultrasonic dispersion, and the ultrasonic time is 20-30 min.
[0026] Further, in step S2, the stirring speed is 800-1000 rpm.
[0027] Further, in step S2, the stirring temperature is 0-8℃.
[0028] Further, in step S2, the reaction time is 2-4 h.
[0029] Further, in step S3, the calcination is carried out in a nitrogen atmosphere.
[0030] Further, in step S3, the polyaniline / molybdenum trioxide composite precursor is vacuum dried at 70-90℃ before calcination.
[0031] Further, in step S3, the calcination temperature is 700-800℃.
[0032] Further, in step S3, the calcination temperature is 700-800℃.
[0033] Further, in step S3, the calcination temperature is 700-800℃.
[0034] The application also provides a graphene-coated molybdenum dioxide nanorod composite material for use in wastewater treatment, wherein the graphene-coated molybdenum dioxide nanorod composite material is used as an electrode material of a capacitive deionization electrode, and under the action of an electric field, lead ions in lead-containing wastewater are adsorbed and removed.
[0035] Further, the capacitive deionization electrode is prepared by mixing graphene-coated molybdenum dioxide nanorod composite material, activated carbon black and polyvinylidene fluoride according to a mass ratio of (75-85):(5-15):(5-15), stirring uniformly after adding a solvent to form a slurry, and coating the slurry on a titanium plate to obtain the capacitive deionization electrode after drying.
[0036] Compared with the prior art, the present application has the following beneficial effects:
[0037] (1) The graphene-wrapped molybdenum dioxide nanorod composite material prepared by the present application has a unique core-shell structure, and has high conductivity of graphene and high adsorption capacity of molybdenum dioxide. In the application process of capacitive deionization, the graphene shell provides a fast electron transmission channel to ensure efficient electron transfer; the molybdenum dioxide core provides a large number of lead ion adsorption sites, which significantly improves the adsorption capacity of lead ions.
[0038] (2) By optimizing the thickness of the graphene layer, the present application can achieve a perfect balance between conductivity and adsorption site exposure, thereby significantly improving the removal efficiency of lead ions.
[0039] (3) The graphene shell of the present application not only improves the conductivity of the material, but also effectively prevents the dissolution and agglomeration of molybdenum dioxide during the recycling process, promotes the heterojunction combination, and improves the process stability and repeatability, thereby greatly improving the cycle stability of the material and prolonging the service life of the material.
[0040] (4) The present application innovatively adopts a two-step method of "in-situ polymerization-high temperature reduction and carbonization", which combines in-situ polymerization and high temperature calcination to realize precise control of the graphene wrapping thickness between 10-80 nm by adjusting the amount of polyaniline, and the preparation process is simple, without the need for complex equipment and expensive reagents, and the reaction conditions are mild, easy to realize industrial production.
[0041] (5) The graphene-wrapped molybdenum dioxide nanorod composite material prepared by the present application has the advantages of fast adsorption rate, large capacity and high selectivity for lead ions in the capacitive deionization process, and the removal rate of lead ions can even reach 100% within 40 minutes, and the removal rate remains above 90% after 10 cycles, showing excellent lead ion removal capacity and cycle stability, providing an efficient and economical new technical solution for lead-containing wastewater purification. BRIEF DESCRIPTION OF DRAWINGS
[0042] Figure 1 X-ray powder diffraction pattern of graphene-wrapped molybdenum dioxide nanorod composite material prepared in Examples 1-3 of the present application.
[0043] Figure 2 Scanning electron microscope microstructure image of graphene-wrapped molybdenum dioxide nanorod composite material prepared in Examples 1-3 of the present application.
[0044] Figure 3 Transmission electron microscope (TEM) image of graphene-wrapped molybdenum dioxide nanorod composite material with different graphene thicknesses in Examples 1-3 and Comparative Examples of the present application.
[0045] Figure 4 The figure is a comparison curve of the capacitive deionization performance of the graphene-wrapped molybdenum dioxide nanorod composite with different graphene thicknesses in the embodiments 1-3 of the present application.
[0046] Figure 5 The figure is a lead ion adsorption retention rate of the graphene-wrapped molybdenum dioxide nanorod composite prepared in the embodiment 2 of the present application and the product obtained in the comparative example 1 after 10 cycles. DETAILED DESCRIPTION
[0047] The present application will be described in detail below with reference to the drawings and specific embodiments. The present embodiments are implemented on the premise of the technical solutions of the present application, and detailed implementation modes and specific operation processes are given, but the protection scope of the present application is not limited to the following examples.
[0048] Unless otherwise specified, the reagents, methods, instruments and equipment used in the present application are the conventional reagents, methods, instruments and equipment in the art. Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0049] The first aspect of the present application provides a graphene-wrapped molybdenum dioxide nanorod composite, which is a core-shell structure with molybdenum dioxide nanorods as the core and a graphene layer as the shell. The graphene layer is formed by high-temperature carbonization of polyaniline, and the thickness of the graphene layer is 10-80 nm.
[0050] The graphene-wrapped molybdenum dioxide nanorod composite prepared in the present application has a unique core-shell structure, in which the molybdenum dioxide nanorod serves as the core and provides high adsorption capacity due to its unique chemical activity; the graphene serves as the shell, not only has high electrical conductivity to provide a fast electron transport channel for the capacitive deionization process, but also plays a protective role for the inner core to enhance the structural stability of the material.
[0051] In some specific embodiments, the diameter of the molybdenum dioxide nanorod is 100-400 nm, and the length of the molybdenum dioxide nanorod is 6-10 μm.
[0052] The second aspect of the present application provides a preparation method of a graphene-wrapped molybdenum dioxide nanorod composite, which comprises the following steps:
[0053] S1: Dissolving a molybdenum source in an aqueous nitric acid solution to perform a hydrothermal reaction to prepare a molybdenum trioxide nanorod precursor;
[0054] S2: Dispersing the molybdenum trioxide nanorod precursor prepared in S1 in an acidic solution, and sequentially adding aniline and ammonium persulfate under stirring conditions to obtain a polyaniline / molybdenum trioxide composite precursor;
[0055] S3: drying the polyaniline / molybdenum trioxide composite precursor obtained in S2, and then performing high-temperature calcination to obtain the graphene-coated molybdenum dioxide nanorod composite material.
[0056] In some specific embodiments, in step S1, the molybdenum source includes any one or more of ammonium heptamolybdate tetrahydrate, ammonium thiomolybdate, sodium molybdate, and calcium molybdate, and is preferably ammonium heptamolybdate tetrahydrate.
[0057] In some specific embodiments, in step S1, the concentration of the molybdenum source in the aqueous nitric acid solution is 0.02-0.35 mol / L.
[0058] In some specific embodiments, in step S1, the concentration of the nitric acid in the aqueous nitric acid solution is 1.44-3.95 mol / L.
[0059] The above concentration ranges of the molybdenum source and the nitric acid are optimized through a large number of experiments, which can ensure that the ammonium heptamolybdate tetrahydrate is fully dissolved and provide a suitable reaction environment for the subsequent hydrothermal reaction, and is conducive to the synthesis of molybdenum trioxide nanorod precursors with regular structure.
[0060] In some specific embodiments, in step S1, the temperature of the hydrothermal reaction is 180-220°C, and is preferably 200°C.
[0061] In some specific embodiments, in step S1, the time of the hydrothermal reaction is 2-10 h, and is preferably 6 h.
[0062] Within the above temperature and time ranges of the hydrothermal reaction, the reaction can be fully carried out, and the generated molybdenum trioxide nanorod precursor has good morphology and structural stability. If the temperature is too low or the time is too short, the reaction is incomplete, and the product has poor purity and morphology; if the temperature is too high or the time is too long, the nanorods may be too thick and not conducive to coating.
[0063] In some specific embodiments, in step S2, the mass ratio of the molybdenum trioxide nanorod precursor, aniline, and ammonium persulfate is (8-10):(3-11):(20-24).
[0064] The molybdenum trioxide nanorod precursor, aniline, and ammonium persulfate form a suitable ratio, which can ensure the smooth progress of the reaction and the quality of the composite precursor. By changing the amount of aniline added, the loading amount of polyaniline can be controlled, and then the thickness of the subsequent graphene coating can be precisely controlled. The amount of ammonium persulfate as an oxidizing agent needs to match the amount of aniline to ensure that aniline can be fully polymerized.
[0065] In some specific embodiments, in step S2, the mass concentration of the molybdenum trioxide nanorod precursor in the acidic solution is 8-12.5 mg / mL.
[0066] In some specific embodiments, in step S2, the acidic solution is a hydrochloric acid solution with a concentration of 1.9-2.1 mol / L. The hydrochloric acid not only provides an acidic environment for the reaction, but also promotes the dispersion of the molybdenum trioxide nanorod and the polymerization of aniline.
[0067] In some specific embodiments, in step S2, the molybdenum trioxide nanorod precursor is dispersed in the acidic solution and then subjected to ultrasonic dispersion for 20-30 min. Through ultrasonic treatment, it is uniformly dispersed in the solution, providing a good reaction interface for the subsequent polymerization reaction.
[0068] In some specific embodiments, in step S2, the stirring speed is 800-1000 rpm. A higher stirring speed can ensure that the reaction system is fully mixed, so that aniline and ammonium persulfate are uniformly distributed in the solution, thereby promoting the uniform polymerization of aniline on the surface of the molybdenum trioxide nanorod.
[0069] In some specific embodiments, in step S2, the temperature during stirring is 0-8℃. The low-temperature environment under ice bath conditions can effectively control the polymerization rate of aniline and avoid excessive reaction that leads to uneven distribution of polyaniline.
[0070] In some specific embodiments, in step S2, the reaction time is 2-4 h. Within this time range, aniline can be fully polymerized to form polyaniline, and a stable composite precursor is formed with the molybdenum trioxide nanorod.
[0071] In some specific embodiments, in step S3, the calcination is carried out in a nitrogen atmosphere.
[0072] In some specific embodiments, in step S3, the polyaniline / molybdenum trioxide composite precursor is first vacuum dried at 70-90℃ before calcination.
[0073] In some specific embodiments, in step S3, the calcination temperature is 700-800℃.
[0074] In some specific embodiments, in step S3, the heating rate of calcination is 3-5℃ / min.
[0075] In some specific embodiments, in step S3, the calcination time is 2-4 h.
[0076] The above calcination conditions are optimized to fully carbonize the polyaniline to form stable graphene, while ensuring that the molybdenum trioxide is completely reduced to molybdenum dioxide, and the morphology and structure of the nanorod are not damaged.
[0077] The third aspect of the present application provides an application of the graphene-coated molybdenum dioxide nanorod composite in wastewater treatment, wherein the graphene-coated molybdenum dioxide nanorod composite is used as an electrode material of a capacitive deionization electrode, and under the action of an electric field, lead ions in lead-containing wastewater are adsorbed and removed.
[0078] In some specific embodiments, the capacitive deionization electrode is prepared by mixing the graphene-coated molybdenum dioxide nanorod composite, activated carbon black and polyvinylidene fluoride according to a mass ratio of (75-85):(5-15):(5-15), stirring uniformly after adding a solvent to form a slurry, and coating the slurry on a titanium plate to obtain the capacitive deionization electrode after drying.
[0079] The graphene-coated molybdenum dioxide nanorod composite of the present application is used as an electrode material in a capacitive deionization device, and under the action of an electric field, lead ions are adsorbed to the surface of the electrode and then enter the molybdenum dioxide lattice, thereby realizing the purification of lead-containing wastewater. In the capacitive deionization process, the graphene shell provides a fast electron transport channel to ensure efficient electron transfer, and the molybdenum dioxide core provides a large number of lead ion adsorption sites to significantly improve the adsorption capacity for lead ions. By optimizing the thickness of the graphene, a perfect balance between electrical conductivity and adsorption site exposure can be achieved, thereby significantly improving the removal efficiency of lead ions.
[0080] Any of the above embodiments can be implemented alone or in any combination of two or more. The above embodiments will be described in more detail below with reference to specific examples.
[0081] Example 1
[0082] This example provides a graphene-coated molybdenum dioxide nanorod composite, which has a molybdenum dioxide nanorod as a core and a 10-20 nm thick graphene layer as a shell. The specific preparation method is as follows:
[0083] (1) Synthesis of molybdenum trioxide nanorod precursor
[0084] 1.75 g of ammonium heptamolybdate tetrahydrate ((NH4)6Mo7O 24 ·4H2O) was dissolved in 60 mL of a nitric acid solution, and after stirring uniformly, it was transferred to a 50 mL polytetrafluoroethylene-lined high-pressure reaction kettle, and reacted at 180℃ for 24 hours. After the reaction was completed, it was naturally cooled to room temperature, centrifuged (8000 rpm, 10 min) to separate the product, washed with deionized water and ethanol three times each, and then dried in a vacuum drying oven at 60℃ for 12 hours to obtain a molybdenum trioxide (MoO3) nanorod precursor.
[0085] (2) Preparation of polyaniline / molybdenum trioxide composite precursor
[0086] 100 mg of the above-mentioned molybdenum trioxide nanorod precursor was added into 10 mL of 2 mol / L hydrochloric acid solution, and ultrasonic treatment was performed in an ultrasonic cleaner for 15 minutes to make the molybdenum trioxide nanorod fully dispersed. Then, the solution was transferred into an ice bath (close to 0°C) and stirred at a stirring speed of 900 rpm.
[0087] 50 μL of aniline (about 0.051 g) was added into 10 mL of 2 mol / L hydrochloric acid solution, and after stirring uniformly, it was added into the above-mentioned solution stirred in the ice bath; 0.24 g of ammonium persulfate was dissolved in 10 mL of 2 mol / L hydrochloric acid solution, and slowly added dropwise into the above-mentioned mixed solution, and after the dropwise addition was completed, stirring was continued for 2 hours to make the aniline in-situ polymerize on the surface of the molybdenum trioxide nanorod, thereby obtaining a polyaniline / molybdenum trioxide composite precursor.
[0088] (3) Preparation of graphene-wrapped molybdenum dioxide nanorod composite material
[0089] The polyaniline / molybdenum trioxide composite precursor was washed with ethanol for three times, and vacuum dried at 80°C for 12 hours. The dried product was placed in a tube furnace, and heated to 750°C at a heating rate of 4°C / min under a nitrogen atmosphere, and kept for 4 hours. The polyaniline was carbonized to form a graphene layer with a thickness of about 10-20 nm, and the molybdenum trioxide was reduced to molybdenum dioxide, thereby obtaining a thin graphene shell-wrapped molybdenum dioxide nanorod.
[0090] Example 2:
[0091] The present example provides a graphene-wrapped molybdenum dioxide nanorod composite material, which is different from the example 1 in that the amount of aniline used in step (2) is 67 μL (about 0.068 g), and the rest of the reagent amount and reaction conditions are unchanged. Finally, a graphene shell layer with a thickness of 40-50 nm is obtained.
[0092] Example 3:
[0093] The present example provides a graphene-wrapped molybdenum dioxide nanorod composite material, which is different from the example 1 in that the amount of aniline used in step (2) is 100 μL (about 0.102 g), and the rest of the reagent amount and reaction conditions are unchanged. Finally, a graphene shell layer with a thickness of 70-80 nm is obtained.
[0094] Figure 1 X-ray powder diffraction of the graphene-wrapped molybdenum dioxide nanorod prepared in the examples 1-3 of the present application. The figure shows the crystal structure characteristics of the molybdenum dioxide nanorod wrapped with different thicknesses of graphene, and the presence of molybdenum dioxide and the crystallinity of the material can be confirmed by the position and intensity of the characteristic peaks.
[0095] Figure 2Scanning electron microscope microstructure images of the graphene-wrapped molybdenum dioxide nanorods prepared in Examples 1-3 of the present application are shown in the following figures. The morphology and size of the nanorods, as well as the graphene wrapping on the surface of the nanorods, can be clearly observed from the figures, which intuitively show the wrapping effect of graphene with different thicknesses. As can be seen from the figures, the diameter of the nanorods in Examples 1-3 gradually increases, with the diameter of the nanorods being 200-250 nm in Example 1, 300-350 nm in Example 2, and 350-400 nm in Example 3.
[0096] Figure 3 Transmission electron microscope (TEM) images of the graphene-wrapped molybdenum dioxide nanorods in Examples 1-3 of the present application are shown in the following figures. The images further reveal the core-shell structure of the material, clearly showing the thickness of the molybdenum dioxide nanorod core and the graphene shell, and confirming the controllability of the graphene wrapping thickness.
[0097] Comparative Example 1
[0098] This comparative example provides a graphene-wrapped molybdenum dioxide nanorod composite material, which differs from Example 1 in that the amount of aniline used in step (2) is 33 μL (about 0.034 g), and the amounts of the other reagents and the reaction conditions remain unchanged.
[0099] Due to the low amount of aniline used in this comparative example, the loading of polyaniline formed by in-situ polymerization on the surface of the molybdenum trioxide nanorods is insufficient, and after high-temperature calcination, the graphene layer formed by carbonization of polyaniline cannot completely coat the surface of the molybdenum dioxide nanorods, resulting in a graphene-wrapped molybdenum dioxide composite material with incomplete graphene wrapping and local exposure.
[0100] Therefore, by using the method of in-situ polymerization combined with high-temperature calcination, the present application achieves precise control of the graphene wrapping thickness (10-80 nm) by adjusting the amount of polyaniline, and successfully prepares a series of graphene-wrapped molybdenum dioxide nanorod composite materials.
[0101] Based on the successful preparation of the graphene-wrapped molybdenum dioxide nanorod composite material described above, the present application further explores its application as an electrode material in the capacitive deionization purification of lead-containing wastewater, with the specific test steps being as follows:
[0102] (1) Preparation of a capacitive deionization electrode: 30 mg of graphene-wrapped molybdenum dioxide nanorods, 3.75 mg of activated carbon black, and 3.75 mg of polyvinylidene fluoride (PVDF) are mixed, 1 ml of N-methyl pyrrolidone (NMP) is added as a solvent, and the mixture is stirred uniformly to form a slurry. The slurry is uniformly coated on a titanium plate with a coating area of 4 cm x 4 cm. The coated titanium plate is then dried in an oven at 80°C for 12 h to obtain a capacitive deionization electrode.
[0103] (2) The prepared electrode was assembled into a capacitive deionization device with a double electrode structure, and the distance between the two electrodes was 0.2 cm. A lead nitrate (Pb(NO3)2) solution with a concentration of 50 mg / L was prepared as a simulated lead-containing wastewater, and the pH value of the solution was adjusted to 5.5. Under a working voltage of 1.2 V, the simulated lead-containing wastewater was passed into the capacitive deionization device at a flow rate of 40 mL / min to carry out a lead ion removal experiment.
[0104] (3) The sample was taken every 5-20 minutes, and the concentration of lead ions in the solution was determined by inductively coupled plasma optical emission spectrometry (ICP-OES), and the lead ion removal rate and the adsorption capacity of the material for lead ions were calculated.
[0105] Figure 4 The capacitive deionization performance comparison curves of the molybdenum dioxide nanorod wrapped by different thicknesses of graphene in embodiments 1-3 of the present application show the influence of the thickness of graphene on the lead ion removal rate. The curves clearly show that with the change of the thickness of graphene, the lead ion removal rate shows a trend of first increasing and then decreasing. Among them, the nanorod wrapped by medium-thickness graphene (thickness of 40-50 nm) has a lead ion removal rate close to 100% within 40 minutes, showing excellent lead ion removal capacity.
[0106] Figure 5 The retention of the lead ion adsorption capacity of the molybdenum dioxide nanorod wrapped by the medium-thickness graphene layer synthesized in embodiment 2 of the present application and the product obtained in comparative example 1 after 10 cycles is shown. After 10 cycles, the retention rate of the lead ion adsorption capacity is still above 94.5%, indicating that the electrode material has good cycle stability. The molybdenum dioxide composite material wrapped by graphene incompletely and partially exposed in comparative example 1 has a lead ion removal rate of less than 65% within 60 minutes, and the retention rate of the adsorption capacity is less than 80% after 10 cycles. Therefore, it can be known that the graphene-wrapped molybdenum dioxide nanorod composite material of embodiment 2 has excellent cycle stability, and the cycle stability of the material prepared in comparative example 1 is poor.
[0107] In summary, the present application successfully prepared a series of graphene-wrapped molybdenum dioxide nanorod composite materials by combining in-situ polymerization and high-temperature calcination, optimized the performance by adjusting the thickness of graphene, overcame the shortcomings of existing electrode materials, provided a new technical scheme for efficient purification of industrial lead-containing wastewater, and had a broad application prospect.
[0108] The foregoing description of the embodiments has been presented for the purpose of illustration and description. It is not intended to be exhaustive or to limit the application to the precise form disclosed. Modifications and variations are possible in light of the above teachings or can be acquired from practice of the application. As well, the description is presented in the context of the preferred embodiments as a number of alternatives. It is not intended to limit the application to the precise form described.
Claims
1. A graphene-coated molybdenum dioxide nanorod composite, characterized by, The composite material is a core-shell structure, taking the molybdenum dioxide nanorod as the core and the graphene layer as the shell. The graphene layer is formed by high-temperature carbonization of polyaniline, and the thickness of the graphene layer is 10-80 nm.
2. The graphene-coated molybdenum dioxide nanorod composite of claim 1, wherein, The diameter of the molybdenum dioxide nanorod is 100-400 nm, and the length of the molybdenum dioxide nanorod is 6-10 μm.
3. A method for preparing the graphene-wrapped molybdenum dioxide nanorod composite of claim 1 or 2, characterized by, The preparation method comprises the following steps: S1: Dissolving a molybdenum source in an aqueous nitric acid solution to perform a hydrothermal reaction, thereby preparing a molybdenum trioxide nanorod precursor; S2: Dispersing the molybdenum trioxide nanorod precursor prepared in S1 in an acidic solution, and then adding aniline and ammonium persulfate under stirring conditions, thereby obtaining a polyaniline / molybdenum trioxide composite precursor; S3: Drying the polyaniline / molybdenum trioxide composite precursor obtained in S2, and then performing high-temperature calcination, thereby obtaining the graphene-coated molybdenum dioxide nanorod composite material.
4. The method of claim 3, wherein the graphene-wrapped molybdenum dioxide nanorod composite is prepared by the steps of: (a) preparing a graphene solution; (b) preparing a molybdenum dioxide nanorod solution; (c) mixing the graphene solution and the molybdenum dioxide nanorod solution; and (d) drying the mixture. In step S1, the molybdenum source comprises any one or more of ammonium heptamolybdate tetrahydrate, ammonium thiomolybdate, sodium molybdate, and calcium molybdate; The concentration of the molybdenum source in the aqueous nitric acid solution is 0.02-0.35 mol / L, and the concentration of nitric acid in the aqueous nitric acid solution is 1.44-3.95 mol / L.
5. The method of claim 3, wherein the graphene-wrapped molybdenum dioxide nanorod composite is prepared by the steps of: (a) preparing a graphene solution; (b) preparing a molybdenum dioxide nanorod solution; (c) mixing the graphene solution and the molybdenum dioxide nanorod solution; and (d) drying the mixture. In step S1, the temperature of the hydrothermal reaction is 180-220 ℃; The time of the hydrothermal reaction is 2-10 h.
6. The method of claim 3, wherein the graphene-wrapped molybdenum dioxide nanorod composite is prepared by the steps of: (a) preparing a graphene solution; (b) preparing a molybdenum dioxide nanorod solution; (c) mixing the graphene solution and the molybdenum dioxide nanorod solution; and (d) drying the mixture. In step S2, the mass ratio of the molybdenum trioxide nanorod precursor, aniline, and ammonium persulfate is (8-10):(3-11):(20-24).
7. The method of claim 3, wherein the graphene-wrapped molybdenum dioxide nanorod composite is prepared by the steps of: (a) preparing a graphene solution; (b) preparing a molybdenum dioxide nanorod solution; (c) mixing the graphene solution and the molybdenum dioxide nanorod solution; and (d) drying the mixture. In step S2, the acidic solution is a hydrochloric acid solution with a concentration of 1.9-2.1 mol / L; The rotation speed of the stirring is 800-1000 rpm; The temperature during the stirring is 0-8 ℃; The time of the reaction is 2-4 h.
8. The method of claim 3, wherein the graphene-wrapped molybdenum dioxide nanorod composite is prepared by the steps of: (a) preparing a graphene solution; (b) preparing a molybdenum dioxide nanorod solution; (c) mixing the graphene solution and the molybdenum dioxide nanorod solution; and (d) drying the mixture. In step S3, the temperature of the calcination is 700-800 ℃; The heating rate of the calcination is 3-5 ℃ / min; The time of the calcination is 2-4 h.
9. The use of the graphene-wrapped molybdenum dioxide nanorod composite material according to claim 1 or 2 in wastewater treatment, characterized in that, The graphene-coated molybdenum dioxide nanorod composite material is used as an electrode material of a capacitive deionization electrode, and can adsorb and remove lead ions in lead-containing wastewater under the action of an electric field.
10. Use of the graphene-wrapped molybdenum dioxide nanorod composite material according to claim 9 in wastewater treatment, characterized in that, The capacitive deionization electrode is prepared by the following method: Mixing the graphene-coated molybdenum dioxide nanorod composite material, activated carbon black, and polyvinylidene fluoride according to a mass ratio of (75-85):(5-15):(5-15), adding a solvent, and stirring uniformly to form a slurry; Coating the slurry on a titanium plate, and drying to obtain the capacitive deionization electrode.